Ascorbic acid specifically reduces the misclassification of nonirritating reactive chemicals in the OptiSafe™ macromolecular eye irritation test. (April 2022) - Lebrun, Stewart; Chavez, Sara; Chan, Roxanne; Nguyen, Linda; Jester, James V.
Abstract: Recently, we showed that the addition of physiological concentrations of ascorbic acid, a tear antioxidant, to the OptiSafe™ macromolecular eye irritation test reduced the false-positive (FP) rate for chemicals that had reactive chemistries, leading to the formation of reactive oxygen species (ROS) and molecular crosslinking. The purpose of the current study was to 1) increase the number of chemicals tested to comprehensibly determine whether the antioxidant-associated reduction in OD is specific to FP chemicals associated with ROS chemistries and 2) determine whether the addition of antioxidants interferes with the detection of true positive (TP) and true negative (TN) ocular irritants. We report that when ascorbic acid is added to the test reagents, retesting of FP chemicals with reactive chemistries show significantly reduced OD values ( P  < 0.05). Importantly, ascorbic acid had no significant effect on the OD values of TP or TN chemicals regardless of chemical reactivity. These findings suggest that supplementation of ascorbic acid in alternative ocular irritation tests may help improve the detection of TN for those commonly misclassified reactive chemicals. Highlights: A previous study found that a tear-related antioxidant (ascorbic acid) reduced the false-positive rate of the OptiSafe macromolecular eye irritation test. In the current study, chemicals from a prior validation study were retested with ascorbic acid. Results indicate that the addition of ascorbic acid specifically reduced the false-positive rate.